The impact of behavioral sciences on criminal law - Farahany, Nita A. (New York ; Oxford : Oxford University Press, 2009)
This volume is essential reading for anyone interested in the ongoing genomics and neuroscience revolution and its implications for criminal law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal behavior -- Genetic aspects; Criminal psychology; Criminal behavior; Behavior genetics